Does VEGF concentration in pre-eclamptic serum induce sVCAM-1 production in endothelial cell culture? (Faculty of Medicine Universitas Indonesia, 2005)
Serum concentrations of VEGF (Vascular Endothelial Growth Factor) are elevated in preeclampsia. In addition to inducing mitosis and increase permeability of endothelial cells, VEGF was reported to activate endothelial cells to produce cell adhesion molecules. Cell adhesion molecules play an important role in the inflammation process by inducing adherence of leukocytes in blood stream to the endothelial cells. The aim of this study is to investigate the effect of VEGF in serum from preeclamptic patients on sVCAM-1 (soluble vascular adhesion molecules-1) production in endothelial cell culture. Twelve sera from women with preeclampsia and 11 from women with normal pregnancy (controls) in 20% concentration were added to human umbilical vein endothelial cell culture (HUVEC) and incubated for 24 hours. All subjects have agreed to participate in this study and signed the informed consent form. sVCAM-1 concentration in the supernatant was measured by ELISA. VEGF concentration tends to be higher in preeclamptic serum than control, but the difference is not stastitically significant. The production of sVCAM-1 by endothelial cells exposed to preeclamptic serum was significantly higher than the production by endothelial cells exposed to serum from control (p<0.05). No correlation was found between the difference in VEGF concentrations in preeclamptic and control sera, and sVCAM-1 production by endothelial cell culture. (Med J Indones 2005; 14: 3-6) Keywords: endothelial cell, preeclampsia, VCAM, VEGF